Direct-write formation of integrated bottom contacts to laser-induced graphene-like carbon. (1st October 2022) - Murray, Richard; O'Neill, Orla; Vaughan, Eoghan; Iacopino, Daniela; Blake, Alan; Lyons, Colin; O'Connell, Dan; O'Brien, Joe; Quinn, Aidan J
Abstract: We report a simple, scalable two-step method for direct-write laser fabrication of 3D, porous graphene-like carbon electrodes from polyimide films with integrated contact plugs to underlying metal layers (Au or Ni). Irradiation at high average CO2 laser power (30 W) and low scan speed (∼18 mm s) −1 leads to formation of 'keyhole' contact plugs through local ablation of polyimide (initial thickness 17 μ m) and graphitization of the plug perimeter wall. Top-surface laser-induced graphene (LIG) electrodes are then formed and connected to the plug by raster patterning at lower laser power (3.7 W) and higher scan speed (200 mm s) −1 . Sheet resistance data (71 ± 15 Ω sq.) −1 indicates formation of high-quality surface LIG, consistent with Raman data which yield sharp first- and second-order peaks. We have also demonstrated that high-quality LIG requires a minimum initial polyimide thickness. Capacitance data measured between surface LIG electrodes and the buried metal film indicate a polyimide layer of thickness ∼7 μ m remaining following laser processing. By contrast, laser graphitization of polyimide of initial thickness ∼8 μ m yielded devices with large sheet resistance (>1 kΩ sq.) −1 . Raman data also indicated significant disorder. Plug contact resistance values were calculated from analysis of transfer line measurement data for single- and multi-plug test structures. Contacts to buried nickel layers yielded lower plug resistances (1-plug: 158 ± 7 Ω, 4-plug: 31 ± 14 Ω) compared to contacts to buried gold (1-plug: 346 ± 37 Ω, 4-plug: 52 ± 3 Ω). Further reductions are expected for multi-plug structures with increased areal density. Proof-of-concept mm-scale LIG electrochemical devices with local contact plugs yielded rapid electron transfer kinetics (rate constant k 0 ∼ 0.017 cm s −1 ), comparable to values measured for exposed Au films ( k 0 ∼0.023 cm s) −1 . Our results highlight the potential for integration of LIG-based sensor electrodes with semiconductor or roll-to-roll manufacturing.